A crown of ivy and glass [large type] - Legrand, Claire, 1986- (The Middlemist trilogy, 2023)
"Every year on St. Walpurga's Eve, Caldella's Witch Queen lures a boy back to her palace. An innocent life to be sacrificed on the full moon to keep the island city from sinking. Lina Kirk is convinced her brother is going to be taken this year. To save him, she enlists the help of the mysterious Thomas Lin, the boy she secretly loves, and the only person to ever escape from the palace. Working together they save her brother, but they draw the queen's attention, and Thomas is then chosen as the sacrifice. Queen Eva casted away her heart when her sister died to save the boy she loved. Now as queen, she won't make the same mistake. With the tide rising higher than ever before and the islanders whispering that Eva's magic is failing, she's willing to sacrifice anyone if it means saving herself and her city. When Lina offers herself in exchange for Thomas's freedom, the two girls await the full moon together. Against their will, they find themselves falling for each other. As water floods Caldella's streets and the dark tide demands its sacrifice, they must choose whom to save" --